1993
DOI: 10.1159/000227175
|View full text |Cite
|
Sign up to set email alerts
|

Ondansetron: A Cost-Effective Advance in Anti-Emetic Therapy

Abstract: A cost-effectiveness analysis is one form of full economic evaluation where drug acquisition costs and the costs that are incurred as a result of using a particular treatment are assessed together with clinical efficacy. This paper reviews two such studies. One of the studies was a prospective randomised cost-effectiveness study which compared ondansetron (8 mg i.v. 0, 4 and 8 h following chemotherapy) with metoclopramide (3 mg/kg i.v. followed by an infusion of 0.5 mg/kg/h for 8 h) over the first 24 h followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 6 publications
0
5
1
1
Order By: Relevance
“…This was mainly attributable to the high differential cost between the original granisetron (Kytril ® ) and generic metoclopramide or dexamethasone marketed in Malaysia. Unlike most of the previous pharmacoeconomic studies of antiemetics in chemotherapy which had favored the new treatment (Cox and Hirsch, 1993;Cunningham et al, 1993;Lordick et al, 2007;Lopes et al, 2012;Humphreys et al, 2013), our results had indicated a high ICER (MYR 430.66 per successfully treated patient) of granisetron-based regimen relative to standard regimen. To date, Malaysia does not have a published threshold to determine costeffectiveness of antiemetics.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…This was mainly attributable to the high differential cost between the original granisetron (Kytril ® ) and generic metoclopramide or dexamethasone marketed in Malaysia. Unlike most of the previous pharmacoeconomic studies of antiemetics in chemotherapy which had favored the new treatment (Cox and Hirsch, 1993;Cunningham et al, 1993;Lordick et al, 2007;Lopes et al, 2012;Humphreys et al, 2013), our results had indicated a high ICER (MYR 430.66 per successfully treated patient) of granisetron-based regimen relative to standard regimen. To date, Malaysia does not have a published threshold to determine costeffectiveness of antiemetics.…”
Section: Discussioncontrasting
confidence: 93%
“…In our study, whilst the ratio of drug acquisition costs for granisetron-based and standard regimens was 40.70, the corresponding ratio of total cost for two sets of treatment was reduced to 8.68 (relative change of 468.9%). This again clearly demonstrated that judging the differential cost between two treatment alternatives based on drug acquisition costs alone could be misleading (Cox and Hirsch, 1993).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, as noted in the above studies, the use of ondansetron can be associated with a decrease in need for hospitalization and therefore may be cost-effective (35,(67)(68)(69). Cost-effectiveness studies comparing ondansetron with metoclopramide in oncology patients have shown that ondansetron administered three times a day is at least as costeffective as metoclopramide, whereas twice-a-day regimens of ondansetron are more cost-effective (78). The doses and route of administration of ondansetron in the above-mentioned investigations can be seen in Table 7.…”
Section: As Abovementioning
confidence: 97%
“…Cost-effectiveness studies comparing ondansetron with metoclopramide in oncology patients have shown that ondansetron administered three times a day is at least as cost-effective as metoclopramide, while twice-a-day regimens are more cost-effective. 27 Hospital acquisition costs for ondansetron are approximately US$4.01 per milligram for intravenous ondansetron and less for oral preparations, but patient charges vary greatly nationwide. 28 Given the cost of intravenous fluid therapy, especially if it includes admission, 5 single-dose ondansetron at a cost of less than US$20 is an attractive alternative.…”
Section: O N D a N S E T R O N T O C O N T R O L V O M I T I N G I N mentioning
confidence: 99%